The effect of in vitro enzyme digestion on antioxidant and anticholinesterase potential of tomato (Lycopersicum esculentum) fruit and two commercially processed tomato pastes - Sule O. Salawu; Olatunde F. Faloye; Bukola B. Ola-Salawu; Akintunde A. Akindahunsi (International Journal of Food Studies)
Tomato is a horticultural crop of interest, that is widely consumed fresh or as processed products. The present investigation was to evaluate the antioxidant indices (total phenolic content, flavonoid content, ferric reducing antioxidant power, radical scavenging activities, inhibitory action against lipid oxidation) and anti-cholinesterase action (acetylcholinesterase and butyrylcholinesterase) of tomato fruits (ripe and unripe) and  pastes (paste 2 and paste 1) after simulated gastrointestinal digestion. The total phenolic content (mg/g GAE) of the In vitro digested tomato fruits and pastes showed higher values (ripe tomato: 61.08; tomato paste1: 56.02; tomato paste 2: 60.36; unripe tomato: 38.97) than the ethanolic extracts, with digested ripe tomato ranking higher. Similar results were also obtained for total flavonoid content, ferric reducing antioxidant power, and the radical scavenging activities (DPPH*, ABTS˙+, NO*, OH*), with the in vitro digested samples ranking high. The ability of the enzyme digested and ethanolic extracts of tomato fruits and pastes to inhibit iron and sodium nitroprusside induced lipid oxidation in rat’s liver and brain homogenate increased in a concentration dependent manner, with the enzyme digested tomato fruits and pastes ranking high. Similarly, the ability of the in vitro digested tomato fruit and pastes to enhance activities of the antioxidant enzymes (GPx, GSH, SOD and Catalase) and to inhibit the formation of cholinesterases ranked high. The result of this investigation showed that the studied tomato fruit and pastes possess antioxidant and anti-cholinesterase activities that would be bio-available after the gastrointestinal digestion and by implication could be harnessed as functional food.